Modulation of TvRAD51 Recombinase in Trichomonas vaginalis by Zinc and Cadmium as a Potential Mechanism for Genotoxic Stress Response - Jonathan Puente-Rivera; José Jesús Flores-Vega; Marcos Morales-Reyna; Elisa Elvira Figueroa-Angulo; Yussel Pérez-Navarro; Alfonso Salgado-Aguayo; Ángeles Carlos-Reyes; Maria Elizbeth Alvarez-Sánchez (Pathogens)
Trichomonas vaginalis, the protozoan responsible for trichomoniasis, encounters fluctuating levels of metal cations in the male urogenital tract, notably zinc (Zn2+) and cadmium (Cd2+), which may induce genotoxic stress. While zinc is a key physiological component of the male reproductive tract, both Zn2+ and Cd2+ can become genotoxic at elevated concentrations. However, their effect on DNA repair mechanisms in T. vaginalis remains poorly understood. This study characterizes, for the first time, the expression and modulation of the recombinase TvRAD51, a homologous recombination (HR) key enzyme, in response to UV irradiation and sublethal concentrations of Zn2+ (1.6 mM) and Cd2+ (0.1 mM). In silico analyses confirmed the presence and conserved structure of the tvrad51 gene and its interaction with HR-related proteins, such as TvBLM and TvBRCA2. Quantitative RT-PCR, Western blot, and immunofluorescence assays revealed that TvRAD51 is upregulated at both transcript and protein levels following UV- and cation-induced DNA damage, with distinct temporal expression patterns for Zn2+ and Cd2+ exposure. Notably, TvRAD51 showed nuclear localization at early time points post-exposure, suggesting active participation in DNA repair processes. These findings demonstrate that TvRAD51 is a central component of the genotoxic stress response in T. vaginalis, potentially contributing to parasite survival and adaptation in hostile environments through homologous recombination repair pathways.